Thermal decomposition and chemical stabilization of mercurocuprate high-temperature superconductors - Peacock, G; Haydon, S; Ellis, A; Gameson, I; Edwards, P (IOP, 2000)
We have investigated the thermal decomposition of the mercurocuprate phases HgBa2Ca2Cu3O8+δ, HgBa2CuO4+δ and (Hg0.8Re0.2)Sr2CuO4+δ. In each compound, decomposition is initiated by the breaking of weak Hg-O bonds, but is driven to completion by the formation of thermodynamically stable barium carbonate phases (BaCO3, BaCuO2.(CO3)x). We show that the barium-free mercurocuprate (Hg0.8Re0.2)Sr2CuO4+δ is significantly more thermally stable than HgBa2CuO4+δ, allowing heat treatments at temperatures of at least 800 °C for moderate periods of time and with only very minor decomposition observed. Further, the mechanism of decomposition for the Ba-free compound appears to be kinetically controlled, not suffering from the thermodynamic sinks (highly thermodynamically stable barium carbonates) available to Ba-based compounds.